2010
DOI: 10.1375/twin.13.2.131
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence that Social Desirability Response Set Explains the General Factor of Personality and Its Affective Correlates

Abstract: In two studies, the General Factor of Personality (GFP) remained intact after controlling for the Lie scale from the Eysenck Personality Questionnaire, despite the Lie Scale showing significant correlations with the GFP defining traits. In Study 1, a re-analysis of 29 self-ratings from 322 pairs of twins (644 individuals) yielded a GFP both before and after controlling for social desirability. In Study 2, four measures of affect in 133 university students loaded on a GFP both before and after controlling for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…The results of the present study are inconsistent with this theory as the bivariate partial correlations between the GFP and the Dark Triad, although somewhat attenuated, persisted when social desirability was controlled for. This is consistent with previous research that has suggested that although the GFP is related to the social desirable responding, it is not solely a product of this bias (Rushton & Erdle, 2009;Rushton & Erdle, 2009;Schermer & Vernon, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the present study are inconsistent with this theory as the bivariate partial correlations between the GFP and the Dark Triad, although somewhat attenuated, persisted when social desirability was controlled for. This is consistent with previous research that has suggested that although the GFP is related to the social desirable responding, it is not solely a product of this bias (Rushton & Erdle, 2009;Rushton & Erdle, 2009;Schermer & Vernon, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that although the GFP is related to social desirability, the GFP cannot be explained by social desirability alone. Further evidence in support of the GFP was found by Rushton and Erdle (2009) who examined multiple informants (self-, teacher-, and parent-ratings) and found that a GFP accounted for 54% of the reliable variance and was found regardless of the source of data.…”
Section: Criticisms Of the Gfpmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, we were able to extract a heritable GFP from the data, which mirrors the results of previous behavioral genetic studies on this general factor (e.g., Veselka et al, 2009a;2009b). This finding lends support to the notion of an overarching general factor of personality, Dark Triad Versus the Supernumerary Personality Inventory which may have important evolutionary implications (Rushton & Erdle, 2010).…”
Section: Relations Between the Dark Triad And Spi And Their Potentialsupporting
confidence: 83%
“…Those high on the GFP experience positive affect and have expectations of future reward, while those low on the GFP experience negative affect and have expectations of future punishment. Subsequently, Rushton and Erdle (2010) found that those who score high on the GFP were not only high in self -esteem and positive affect, but low in depression as measured by the Beck Depression Inventory. Several cross -national twin studies have found that 50 percent of the GFP variance is due to genetic infl uence and 50 percent to non -shared environmental infl uence.…”
Section: The Gfp and Subjective Well -Beingmentioning
confidence: 99%